Performance of an LLMS Beamformer in the Presence of Element Gain and Spacing Variations - Srar, Jalal; Chung, Kah-Seng; Mansour, Ali (IEEE, 2011)
This paper studies the influence of tolerances in inter-element spacing and element gain on the operation of the LLMS adaptive beamforming algorithm. Both random and worst case scenarios of inter-element spacing and element gain variations have been considered. Computer simulations show that these practical tolerances have greater influence on the beam pattern than the error vector magnitude (EVM). Simulated results also confirm the superior performance of the LLMS algorithm over the recursive least square (RLS) and the constrained stability LMS (CSLMS) algorithms when operating in the presence of multiple sources of co-channel interference.